O povoado pré-histórico de Leceia. Cinquenta anos de trabalhos arqueológicos (1972-2022) - Cardoso, João Luís (2022)
The history of the investigations carried out in the prehistoric settlement of Leceia by the Author since 1972, is described, as well as the actions of safeguarding, valuing and disseminating the knowledge of the archaeological station, carried out after the creation in 1988 of the Center for Archaeological Studies of the Municipality of Oeiras (CEACO/CMO). Specific initiatives carried out since then are described, from the restoration of archaeological structures to guided tours, colloquiums and publications of a diverse nature depending on the respective recipients, most especially the school population. Of particular interest is the description, year after year, of the progress of the archaeological excavations carried out between 1983 and 2002, as well as the results obtained and briefly presented, with regard to the identified structures and their diachrony, phases of occupation evidenced by the stratigraphy and respective chronology absolute and cultural integration, based on the typology of some artifacts. In this way, the prehistoric settlement of Leceia corresponds to the first of its kind, given its dimensions and complexity, in which it was possible, through the correlation of evidence collected during the excavations, to obtain safe and accurate information on the evolution of its occupation, evidencing a pre-defined organization of the space that would be successively occupied, of a proto-urban character, placing it among one of the most important Chalcolithic fortified settlements in Western Europe.